Prediction of fracture parameters of concrete by Artificial Neural Networks - Ince, R (Pergamon-Elsevier Science Ltd, 2004)
Modelling of material behaviour generally involves the development of a mathematical model derived from observations and experimental data. An alternative way discussed in this paper is Artificial Neural Network (ANN)-based modelling which is a subfield of artificial intelligence. The main benefit in using an ANN approach is that the network is built directly from experimental data using the self-organising capabilities of the ANN. In this paper the Two-Parameter Model (TPM) in the fracture of cementitious materials is modelled with a back-propagation ANN. The results of an ANN-based TPM look viable and very promising. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: concrete; fracture mechanics; two-parameter model; artificial intelligence; artificial neural networks